Diffusion and Adoption of Biochar Innovations in Agriculture at Gunungsari Village , Bumiaji Subdistrict, Batu City, East Java, Indonesia - Lestari, Adyla Mita; Wisadirana, Darsono; Kanto, Sanggar; Mu'adi, Solih (RA Journal of Applied Research, 2022)
Biochar is a solid material obtained from the carbonization process of biomass. In the process of making biochar one of them can be done by using cow animal feed waste such as corn nuggets. The process of diffusion and adoption of biochar innovations by using bonggol (janggel) corn ini is very suitable for areas that have large types of livestock such as dairy cows as done in Gunungsari Village, Bumiaji Subdistrict, Batu City. For this reason, the focus of this research study is to analyze in depth related to diffusion proses and the adoption of farmers' biochar innovations in adopting biochar in Gunungsari Village, Bumiaji District, Batu City. The type of research used in this study is to use qualitative methods with phenomenological approaches. The results showed that the elements of the innovation diffusion process in biochar were known that one of the biochar innovations was the right way to overcome various existing problems. There are two main problems that can be overcome by innovation, namely alleviating the problem of animal feed waste that exists, and overcoming the scarcity of fertilizer that occurs in the community of Gunungsari Village. Then in terms of communication channels, it is done by providing knowledge to Gunungsari farmers, so as to grant the trust and attention of the recipients of this innovation. Furthermore, in the existing social system in Gunungsari there is a social structure that provides levels of social status to its members. Gunungsari village leaders are the first people to be targeted in conducting communication patterns. In his sosilization, sanggat village leaders played a role in convincing to conduct trials first at the head of the farmer group. So, in the end, this biochar innovation can be accepted by the community and used well even through a long period of time.